2001
DOI: 10.1111/j.1651-2227.2001.tb00262.x
|View full text |Cite
|
Sign up to set email alerts
|

Importance of insulin content in infant diet: suggestion for a new infant formula

Abstract: Oral insulin promotes intestinal maturation and may prevent diabetes in animal models. The aim of this study was to evaluate the concentration of insulin in human milk and in different infant formulas. Our results show that the concentration of insulin in human milk is significantly higher (60.23 ± 41.05 μU/ml mean ± SD) compared with cow's milk (16.32 + 5.98 μU/ml mean ± SD) and that insulin is hardly detectable in infant formulas. We propose the addition of human insulin to infant formula to match its compos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 12 publications
1
19
2
Order By: Relevance
“…It has been reported that increased responsiveness of rat immature enterocytes to insulin, usually seen at the onset of weaning in suckling animals, could be related to high membrane concentrations of the insulin receptor (19). However, the effects of oral insulin on gut maturation and intestinal mucosal enzyme expression have usually been demonstrated in suckling mice, rat, piglets, calves, and pigs (3,(17)(18)(19)(20). Furthermore, when insulin was given intraperitoneally to rats, the effects on intestinal cells was limited to suckling animals (7).…”
Section: Discussionmentioning
confidence: 98%
“…It has been reported that increased responsiveness of rat immature enterocytes to insulin, usually seen at the onset of weaning in suckling animals, could be related to high membrane concentrations of the insulin receptor (19). However, the effects of oral insulin on gut maturation and intestinal mucosal enzyme expression have usually been demonstrated in suckling mice, rat, piglets, calves, and pigs (3,(17)(18)(19)(20). Furthermore, when insulin was given intraperitoneally to rats, the effects on intestinal cells was limited to suckling animals (7).…”
Section: Discussionmentioning
confidence: 98%
“…However, the concentration of insulin in human milk is also significantly higher (60.23±41.05 micro unit/mL) whereas it is low in cow milk (16.32±5.98 micro unit/mL) (Shehadeh et al, 2001) but probably because of coagulation in stomach it is not available for absorption in the intestine. Intestinal absorption of large proteins and, therefore, insulin is only possible in the first few days of life (Lawrence and Lawrence, 2010).…”
Section: Discussionmentioning
confidence: 94%
“…Diabetes mellitus interrupts normal child development and carries the threat of severe complications in the active period of their lives. It is therefore, urgently needed to search for safe and more effective therapies for DM, either as complementary or alternative to existing treatment programs as no drug has been shown to modify the course of diabetic complications [13,18].An alternative to current insulin treatment of DM is Camelusdromedarius milk [18][19][20][21][22][23][24][25][26][27][28]. Moreover, Camelusdromedarius milk has shown to have exceptional broad therapeutic qualities on other serious human diseases [24,[29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%